Dietary fiber sources modulate short-chain fatty acid profiles and the fecal microbiota in sows during late gestation - Idael Matheus Góes Lopes; Marcelo Dourado de Lima; Soraia Viana Ferreira; Rafaela Jorge Sarsur de Freitas Ribeiro; Lesleyane Dâmaris Teixeira Santos; Artur Cavalcanti de Souza; Luisa Lopes da Rocha dos Santos; Celmo Guedes Sant'Ana Filho; Murilo José Marques Maia; Karine Aparecida Rodrigues de Souza; Walter Motta Ferreira; Dalton de Oliveira Fontes (Bioactive Carbohydrates and Dietary Fibre, 2026)

Nuclear receptor disruption contributes to 2,4-dichlorophenol-induced developmental toxicity: Evidence from network toxicology and zebrafish analysis - Rafael Xavier Martins; Romério de Oliveira Lima Filho; Cleyton de Sousa Gomes; Matheus Carvalho; Maria Eduarda de Souza Maia; Bianca Mataribu; Catarina Serrão; Marcos Vinicius Porto Medeiros; Milena Pereira Arruda; Ana Julia Antunes de Magalhães; Juliana Alves da Costa Ribeiro Souza; Thaís Feitosa Guimarães; et al. (Environmental Research, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Possible role of domestic cats in the epidemiology of leishmaniasis: evidence of genital lesions and vertical transmission - Júlia Campos Bezerra; Clarissa Helena Santana; Ana Carolina Amado-Gomes; Tatyane Martins Cirilo; Ana Laura Grossi de Oliveira; Marianna de Carvalho Climaco; Amanda Cardoso de Melo; Jenner Karlisson Pimenta dos Reis; Pedro Paulo de Abreu Telles; Wagner Luiz Tafuri; Jonas Pereira da Silva Neto; Leticia Tiemi Kyuna; et al. (Veterinary Research Communications, 2026)

Industrial-scale fermentation of Arara coffee in A 15,000 L bioreactor: Impacts of process variables on quality and sensory profiles - Laila Alonso; Gisele Xavier Ribeiro Costa; Karolina Prisco Borba; Luiza Manuela Alves Braga Cardoso; Marcelo Antônio Duarte da Cruz; Christiano Vieira Pires; Pedro Luiz Lima Bertarini; Matheus de Souza Gomes; Laurence Rodrigues Amaral; Renata Abadia Reis Rocha; Liliane Maciel de Oliveira; Líbia Diniz Santos (Food Research International, 2026)

Seasonality in the reproductive cycles of the coconut palm: an analysis of basal temperatures, duration and harvest estimates in the Northeast of Pará, Brazil - Gabriel Siqueira Tavares Fernandes; João Vitor Ferreira da Silva; Matheus Lima Rua; Luis Roberto da Trindade Ribeiro; Leandro Monteiro Navarro; Breno Rodrigues de Miranda; Erika de Oliveira Teixeira de Carvalho; João Vitor de Nóvoa Pinto; Paulo Manoel Pontes Lins; Samuel Ortega-Farias; Paulo Jorge de Oliveira Ponte de Souza (International Journal of Biometeorology, 2025)

Bioremediation of brewery wastewater using Arthrospira sp.: Preliminary assessment of biomass as a biofertilizer toward circular economy - Arthur Lima e Silva; Daniel Kurpan; Matheus Ribeiro de Moura; Arthur Costa dos Santos; Thalia de Souza Silva; Bruna de Lemos Novo; Isadora de Oliveira Santo; Lucas Queiroz Balata; Layon Carvalho de Assis; Elisabete Barbarino; Denise Maria Guimarães Freire; Anita Ferreira do Valle (Journal of Applied Phycology, 2025)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Impact of Plant-Derived Compounds on Amyotrophic Lateral Sclerosis - Lucas Matheus Gonçalves de Oliveira; Rodrigo Barreto Carreira; Juciele Valeria Ribeiro de Oliveira; Ravena Pereira do Nascimento; Cleide dos Santos Souza; Emiliano Trias; Victor Diogenes Amaral da Silva; Silvia Lima Costa (Neurotoxicity Research, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Robustness of Bergmann’s and Rapoport’s rules to different geographical range estimates in New World pit vipers - Cleber Ten Caten; Matheus Souza Lima‐Ribeiro; Carlos Yañez‐Arenas; Fabricio Villalobos; Luis Díaz‐Gamboa; Levi Carina Terribile (Journal of Biogeography, 2023)
Aim Bergmann's and Rapoport's rules are two ecogeographical patterns that predict an increase in species body size and range size, respectively, with increasing latitudes. Here, we evaluated whether using different geographical range estimates affects the assessment of Bergmann's and Rapoport's rules at the cross‐species and assemblage levels in New World pit vipers. Location New World. Taxon New World pit vipers (Crotalinae). Methods We estimated geographical ranges for 135 (i.e. ≈93%) Crotalinae species using ecological niche modelling (ENM) and expert maps and assessed alternative hypotheses that could account for Bergmann's and Rapoport's rules. We evaluated both rules using ‘cross‐species’ (i.e. species as units of observation) and ‘assemblage’ (i.e. sites/grid cells as units of observation) approaches. We used phylogenetic generalized least squares (PGLS) analyses and generalized least squares (GLS) analyses to account for phylogenetic and spatial autocorrelation that could affect the evaluation of these rules at the cross‐species and assemblage levels, respectively. Results Expert maps differed significantly from ENM ranges. The cross‐species approach was robust to these different range estimates when Bergmann's and Rapoport's rules were evaluated. The assemblage analyses were more vulnerable to different range estimates, where contrasting results were observed in the assessment of Bergmann's rule but not in the evaluation of Rapoport's rule. Main Conclusions Different geographical range estimates affected mainly the assessment of ecogeographical rules at the assemblage level, whereas the cross‐species analyses were more robust. However, this increased susceptibility of the assemblage approach to different range estimates was only observed when evaluating Bergmann's rule. Thus, our findings suggest that ecogeographical rules can have different levels of sensitivity to different range estimates, which can especially affect the assemblage‐level assessment of these ecogeographical patterns.

Rare and common species are doomed by climate change? A case study with neotropical butterflies and their host plants - Juliane M. F. Bellaver; Matheus de Souza Lima-Ribeiro; Diego Hoffmann; Helena Piccoli Romanowski (Journal of Insect Conservation, 2022)

Impacts of a hydroelectric power plant on the bat community in central Brazil - Marlon Zortéa; Karla de Souza Gomes; Leonardo Aparecido Guimarães Tomaz; Jorge M. M. M. Palmeirim; Matheus S. Lima-Ribeiro (Mammal Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Overcoming the worst of both worlds: integrating climate change and habitat loss into spatial conservation planning of genetic diversity in the Brazilian Cerrado - José Alexandre Felizola Diniz-Filho; Ana Clara de Oliveira Ferraz Barbosa; Lázaro José Chaves; Kelly da Silva e Souza; Ricardo Dobrovolski; Ludmila Rattis; Levi Carina Terribile; Matheus Souza Lima-Ribeiro; Guilherme de Oliveira; Fernanda Thiesen Brum; Rafael Loyola; Mariana Pires de Campos Telles (Biodiversity and Conservation, 2020)

The potential invasiveness of an aquatic macrophyte reflects founder effects from native niche - Luiz Guilherme dos Santos Ribas; Cibele de Cássia-Silva; Danielle Katharine Petsch; Márcio José Silveira; Matheus Souza Lima-Ribeiro (Biological Invasions, 2018)

Predicting where species could go: climate is more important than dispersal for explaining the distribution of a South American turtle - João Fabrício Mota Rodrigues; Matheus Souza Lima-Ribeiro (Hydrobiologia, 2018)

Biogeography of Neotropical Rainforests: past connections between Amazon and Atlantic Forest detected by ecological niche modeling - Thadeu Sobral-Souza; Matheus S. Lima-Ribeiro; Vera Nisaka Solferini (Evolutionary Ecology, 2015)

Differential effects of temperature change and human impact on European Late Quaternary mammalian extinctions - Sara Varela; Matheus Souza Lima‐Ribeiro; JosÉ Alexandre Felizola Diniz‐Filho; David Storch (Global Change Biology, 2015)
Species that inhabited Europe during the Late Quaternary were impacted by temperature changes and early humans, resulting in the disappearance of half of the European large mammals. However, quantifying the relative importance that each factor had in the extinction risk of species has been challenging, mostly due to the spatio‐temporal biases of fossil records, which complicate the calibration of realistic and accurate ecological niche modeling. Here, we overcome this problem by using ecotypes, and not real species, to run our models. We created 40 ecotypes with different temperature requirements (mean temperature from −20 °C to 25 °C and temperature range from 10 °C to 40 °C) and used them to quantify the effect of climate change and human impact. Our results show that cold‐adapted ecotypes would have been highly affected by past temperature changes in Europe, whereas temperate and warm‐adapted ecotypes would have been positively affected by temperature change. Human impact affected all ecotypes negatively, and temperate ecotypes suffered the greatest impacts. Based on these results, the extinction of cold‐adapted species like Mammuthus primigenius may be related to temperature change, while the extinction of temperate species, like Crocuta crocuta , may be related to human impact. Our results suggest that temperature change and human impact affected different ecotypes in distinct ways, and that the interaction of both impacts may have shaped species extinctions in Europe.